Chairman - A Conference Management System - Levačić, Vjekoslav (Array, 2005)
In this paper we present a novel web-based system for conference management that uses open source software. The developed Chairman system provides functionality for online paper submission, peer review, decision making process, submission of final papers, conference registration and payment of fees, preparation of conference proceedings, and on-site participant support during the meeting. The system enables interaction of all participants in various roles such as corresponding author, reviewer, program committee (PC) member, PC chair, and special session chair. Support for e-mail messaging is built in for reminding and other purposes. Chairman system has a modular software architecture based on web application framework called Struts, uses Tomcat servlet/JSP container for application deployment, and MySql database for data storage. Security features have been implemented to keep integrity of information in the system. The system has been used for online support of an international scientific symposium.